2001
DOI: 10.1677/joe.0.1690563
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic activity of high molecular weight forms of insulin-like growth factor-II in amniotic fluid

Abstract: Amniotic fluid (AF) collected from ewes and goats at mid gestation displayed mitogenic activity in mouse fibroblasts. Upon fractionation of this material by size exclusion chromatography, the mitogenic activity was resolved into two peaks, whose activity was inhibited by an anti-IGF type 1 receptor blocking antibody. One of the peaks contained IGF-I and IGF-II (mature form), whereas the other contained high M r precursor forms of IGF-II. The presence in this latter fraction of IGF-binding proteins (IGFBP) sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, after gel filtration on Sephadex G‐10 columns, the void volume seems to possess stimulatory activity, in contrast to the total volume that inhibits cell proliferation. Similar results were obtained with AF from ewes and goats 22 . In addition, the authors have shown that the mitogenic activity in some fractions after gel filtration is potently inhibited by an antibody against IGF type 1 receptor.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, after gel filtration on Sephadex G‐10 columns, the void volume seems to possess stimulatory activity, in contrast to the total volume that inhibits cell proliferation. Similar results were obtained with AF from ewes and goats 22 . In addition, the authors have shown that the mitogenic activity in some fractions after gel filtration is potently inhibited by an antibody against IGF type 1 receptor.…”
Section: Discussionsupporting
confidence: 78%
“…It is known from the literature that AF contains a large number of growth factors, such as bFGF, PDGF, TGF‐β, IGF‐I, and EGF 22–25 . Having already shown that the mitogenicity of AF is due to (more than one) growth factors we proceeded to identify these factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, high molecular weight forms of IGF2 correspond to precursor forms. They are known to be potent mitogens and better activators of the IGF type I receptor than is the fully processed form of IGF2 (Valenzano et al, 1998;Blahovec et al, 2001). To standardize the results, the same amounts of total proteins were used for all samples and the western membranes were stained with Ponceau Red.…”
Section: Research Articlementioning
confidence: 99%
“…Their properties are the same or very similar to those of human IGFBP-1 andIGFBP-3 (Bla-hovec et al, 1999, 2001a). The recent studies have however shown that these mitogenically active proteins are probably high molecular precursor forms of IGF-II (Blahovec et al, 2001b).…”
Section: Classification Of Igfbpsmentioning
confidence: 98%